2022
DOI: 10.16970/entoted.1017243
|View full text |Cite
|
Sign up to set email alerts
|

Cydalima perspectalis (Walker, 1859) (Lepidoptera: Crambidae: Spilomelinae)’ten izole edilen cry1, cry3 ve cry4 genlerini içeren yerel Bacillus thuringiensis (Berliner, 1915) (Bacteria: Bacillaceae) bakterisine ait insektisidal aktivite

Abstract: Cydalima perspectalis (Walker, 1859) (Lepidoptera: Crambidae: Spilomelinae) is a primary pest on boxwood. The larvae of this pest cause damage by eating the leaves. They prevent the plant from performing photosynthesis, gnaw the bark of the shoots, damage the cambium layer and thus dry the boxwood shoots and branches. The boxwood moth, which is an exotic species in Türkiye, was first found in gardens and parks in Istanbul in 2011 and subsequently in Artvin and Düzce in 2015, and Bartın in 2016. The aim of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In a similar study, Hulujan et al (2021) found that most larvae have been infected with Bacillus species. Moreover, Bacillus thuringiensis was isolated from C. perspectalis larvae in natural populations, and 85% mortality was obtained with this isolate in bioassay trials (Usta 2022).…”
Section: Bacterial Entomopathogensmentioning
confidence: 99%
“…In a similar study, Hulujan et al (2021) found that most larvae have been infected with Bacillus species. Moreover, Bacillus thuringiensis was isolated from C. perspectalis larvae in natural populations, and 85% mortality was obtained with this isolate in bioassay trials (Usta 2022).…”
Section: Bacterial Entomopathogensmentioning
confidence: 99%
“…In recent years, a large number of studies have been conducted on the effectiveness of microbial pathogens including viruses, bacteria, and fungi an important agricultural pests (Ince et al 2007 Usta 2022). Many biological control products developed from these microorganisms are used as pesticides in integrated pest management (IPM) programs against various pests, including aphids (Vega et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Eski et al, (2022), reported that Bt Xd3 against Leptinotarsa decemlineata showed 83% and 73% mortality in larvae and adults, respectively, within 10 days when applied at 10 9 cfu/mL -1 concentration. Usta (2022), Bt from Cydalima perspectalis collected from Artvin province and reported that this bacterium showed an 85% mortality rate on the pest. Eski (2023) tested 13 local Bt strains isolated from soil samples for the control of Tuta absoluta and declared that Bt-B3 isolate is a promising biological warfare agent for integrated pest control of T. absoluta in Turkey.…”
Section: Introductionmentioning
confidence: 99%